Pd-BCN / SnO2 gas-sensitive composite material as well as preparation method and application thereof

By preparing Pd-BCN/SnO2 gas-sensitive composite materials, the problem of insufficient H2 detection performance of traditional sensors at low temperatures is solved, and a hydrogen sensing effect with high sensitivity, fast response and good selectivity is achieved.

CN119959311APending Publication Date: 2025-05-09ZHENGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510148288.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

In the prior art, traditional semiconductor metal oxide gas sensitive sensors have problems such as high operating temperature, low sensitivity, long response/recovery time and poor selectivity when detecting hydrogen, which is difficult to meet the needs of efficient detection of H2 at low temperatures.

Method used

The Pd-BCN/SnO2 gas-sensitive composite was used to prepare SnO2 nanoparticles by co-precipitation method, and the precious metal Pd and carbon material BCN were loaded by ultrasonic impregnation method. Finally, the Pd-BCN/SnO2 composite was calcined in a hydrogen atmosphere to obtain the Pd-BCN/SnO2 composite material, which improved the conductivity and hydrogen sensing performance of the material.

Benefits of technology

It has high sensitivity and fast response/recovery performance to H2 at low temperature <120°C. The sensor has a response value of up to 1585.85 to 500ppm H2 at the optimal operating temperature of 75°C. The response recovery time is fast, and has good selectivity and repeatability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005267221320000011
    Figure HDA0005267221320000011
  • Figure HDA0005267221320000012
    Figure HDA0005267221320000012
  • Figure HDA0005267221320000021
    Figure HDA0005267221320000021
Patent Text Reader

Abstract

The invention discloses a Pd-BCN / SnO2 gas-sensitive composite material as well as a preparation method and application thereof, and the preparation method comprises the following steps: adding BCN and SnO2 nanoparticles into an ethanol solution of PdCl2, carrying out ultrasonic treatment to load PdCl2 and BCN onto the surface of SnO2, and then calcining in a hydrogen atmosphere to obtain the Pd-BCN / SnO2 gas-sensitive composite material. The sensing device assembled by the Pd-BCN / SnO2 gas sensitive material provided by the invention can be used for low-temperature H2 monitoring, has a relatively high response value to H2 at a low temperature, has a response value to 500 ppm H2 as high as 1585.85 at an optimal working temperature of 75 DEG C, is short in response recovery time, and has good hydrogen selectivity and repeatability at the temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of gas-sensitive sensors, and in particular relates to a gas-sensitive composite material, a preparation method thereof, and an application thereof in H2 sensing. Background Art

[0002] The rapid depletion of fossil fuels has aroused people's attention to the next generation of green fuels. Hydrogen (H2), as a high-density energy carrier, has a high calorific value and can achieve zero carbon emission during combustion, so it is expected to become a new energy source to replace traditional fossil fuels. However, hydrogen is colorless and odorless, has a high diffusion coefficient, low ignition energy (0.02mJ), and a large explosion range (4-75%). Therefore, in order to avoid safety accidents, it is necessary to monitor the H2 concentration in real time.

[0003] In recent years, resistive semiconductor metal oxide sensors have been widely used in environmental monitoring, food safety, transportation, medical care and other fields due to their advantages such as small size, low cost, fast response speed and long life.

[0004] There are many types of traditional semiconductor metal oxide gas sensors, such as SnO2, ZnO, WO3, TiO2, etc. Although they have certain sensitivity to H2, they have problems such as high operating temperature (>200℃), low sensitivity, long response / recovery time, and poor selectivity. The high operating temperature of the sensor not only increases energy consumption, but also poses safety hazards in practical applications. Therefore, it is necessary to develop a gas-sensitive sensing material that can efficiently detect H2 at low temperatures.

[0005] A Chinese patent application (CN117929487A) discloses an Au-Pt bimetallic co-modified In2O3 nanoflower material for resistive hydrogen sensors, a preparation method, and its application in hydrogen sensing. The material improves the sensing performance of the In2O3 sensor by loading bimetallic Au and Pt. However, the working temperature of the gas-sensitive material is relatively high (about 240°C), which makes it difficult to meet the needs of actual applications.

[0006] In summary, it is necessary to develop a gas-sensitive sensing material that has high sensitivity to H2 and fast response / recovery performance at a relatively low temperature (<120°C). Summary of the invention

[0007] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a gas-sensitive sensor material composite material having high sensitivity to H2 and fast response / recovery performance at a relatively low temperature (<120°C) and a preparation method and application thereof.

[0008] In order to solve the above technical problems, the technical solution proposed by the present invention is:

[0009] A method for preparing a Pd-BCN / SnO2 gas-sensitive composite material comprises the following steps:

[0010] BCN and SnO2 nanoparticles are added to an ethanol solution of PdCl2, and ultrasonic treatment is performed to load PdCl2 and BCN onto the surface of SnO2, and then calcined in a hydrogen atmosphere to obtain the Pd-BCN / SnO2 gas-sensitive composite material;

[0011] In the Pd-BCN / SnO2 gas-sensitive composite material, the mass ratio of Pd to SnO2 is 1-3:100, and the mass ratio of BCN to SnO2 is 1-10:100.

[0012] As a further improvement, the preparation method of the SnO2 nanoparticles is: an anhydrous sodium carbonate solution is added dropwise to an ethylene glycol solution of SnCl4·5H2O to react, and the SnO2 nanoparticles are obtained by calcining.

[0013] As a further improvement, the reaction temperature is -20 to 100°C.

[0014] As a further improvement, the calcination temperature for obtaining SnO2 nanoparticles is 300-500°C.

[0015] As a further improvement, the mass ratio of Pd to SnO2 is 2:100, and the mass ratio of BCN to SnO2 is 5:100.

[0016] As a further improvement, the calcination temperature of the Pd-BCN / SnO2 gas-sensitive composite material obtained by calcination is 100-300°C.

[0017] The Pd-BCN / SnO2 gas-sensitive composite material provided by the invention is prepared by adopting the method described.

[0018] The gas-sensitive element provided by the present invention comprises an alumina ceramic tube and a gas-sensitive coating coated on the outer wall thereof, wherein the gas-sensitive coating comprises the Pd-BCN / SnO2 gas-sensitive composite material.

[0019] The hydrogen sensor provided by the present invention comprises the above-mentioned gas sensitive element.

[0020] The application of the Pd-BCN / SnO2 gas-sensitive composite material, the gas-sensitive element, or the hydrogen sensor provided by the present invention in low-temperature H2 sensing has an operating temperature of <120°C.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention firstly adopts a co-precipitation method to prepare SnO2 nanoparticles, then loads precious metal Pd and carbon material BCN on the SnO2 nanoparticles by ultrasonic impregnation, and finally obtains a Pd-BCN / SnO2 composite material through H2 reduction calcination, thereby increasing the active sites of the SnO2 nanoparticles, and the loading of BCN and precious metal Pd as well as hydrogen reduction increase oxygen vacancies, thereby improving the electrical conductivity of the material and thus enhancing its hydrogen sensing performance.

[0023] The noble metal Pd and carbon material BCN improve the hydrogen sensing performance of SnO2 mainly for the following reasons: First, the noble metal Pd has a unique affinity for H2 and can selectively adsorb H2. In addition, the dissociation of H2 by Pd leads to a "hydrogen overflow effect", which promotes the oxidation reaction. 0 It is more conducive to the adsorption and dissociation of low-temperature H2. A large number of H2 molecules are adsorbed on the Pd-BNC / SnO2 surface and react with it, thereby improving the hydrogen sensing performance. Secondly, the incorporation of low-electronegativity boron atoms in BCN can significantly change the local electronic structure of the metal anchoring site, promoting the Pd 0 The generation and improvement of Pd 0 stability. Moreover, BCN is conductive. After adding BCN, the band gap of the gas-sensitive material becomes narrower, the electron mobility is improved, and free electrons are more easily generated, which is conducive to reducing the working temperature. Finally, SnO2 and BCN are both n-type semiconductors, and the work function of SnO2 (4.9eV) is greater than the work function of BCN (4.39eV). Electrons migrate from the BCN conduction band to the SnO2 conduction band, making the Fermi levels of the two equal. Therefore, electron accumulation will occur at the BCN-SnO2 interface, promoting the reaction between hydrogen and oxygen anions, further improving the sensing performance. The use of Pd-BCN and SnO2 composites also improves hydrogen selectivity. When H2 is adsorbed on Pd-BCN / SnO2 and dissociated, the dissociated H atoms will produce a synergistic effect with the adjacent B atoms in BCN, so that the low-valent Pd in ​​Pd-BCN / SnO2 has more electrons, which can return to the H2 antibonding orbit, thereby promoting the activation of the HH bond.

[0024] The sensor device assembled by the Pd-BCN / SnO2 gas-sensitive material provided by the present invention can be used for low-temperature (<120°C) H2 monitoring, has a high response value to H2 at low temperature, and has a response value of up to 1585.85 to 500ppm H2 at the optimal working temperature of 75°C, a fast response recovery time (49s / 3s), and good selectivity and repeatability for hydrogen at this temperature. Compared with pure SnO2 material (working temperature 200°C), the sensor device assembled by the gas-sensitive material has lower energy consumption and is more conducive to meeting practical application requirements. In addition, the preparation method of the present invention is simple, low-cost, and green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 The response curve of Pd / SnO2 sensors with different loading amounts to 500ppm H2 changes with temperature.

[0027] Figure 2 XRD patterns of Pd / SnO2 and BCN gas-sensitive materials with different BCN loading amounts.

[0028] Figure 3 The response curve of 2wt% Pd / SnO2 and 2wt% Pd / SnO2 gas sensors with different BCN doping amounts to 500ppm H2 varies with temperature.

[0029] Figure 4 Response recovery time curves of (a) 2wt% Pd / SnO2 and (b) 2wt% Pd-5wt% BCN / SnO2 gas sensors to 500ppm H2 at different temperatures.

[0030] Figure 5 Response recovery time curves of 2wt% Pd / SnO2 and 2wt% Pd-5wt% BCN / SnO2 sensors at 75℃ and 100℃.

[0031] Figure 6 This is the energy band diagram of the 2wt% Pd-5wt% BCN / SnO2 gas-sensitive material in Example 2 and the 2wt% Pd / SnO2 gas-sensitive material in Comparative Example 1.

[0032] Figure 7 This is the selectivity graph of 2wt% Pd-5wt% BCN / SnO2 sensor to 500ppm of different gases at 75℃ and relative humidity of 50±5%.

[0033] Figure 8 This is the response recovery curve of 2wt% Pd-5wt% BCN / SnO2 sensor to different concentrations of H2 at 75℃ and relative humidity of 50±5%.

[0034] Fig. 9 This is the repeatability curve of 2wt% Pd-5wt% BCN / SnO2 sensor to 500ppm H2 at 75℃ and relative humidity of 50±5%. DETAILED DESCRIPTION

[0035] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0036] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0037] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0038] In some specific embodiments, the preparation method of the Pd-BCN / SnO2 gas-sensitive composite material of the present invention comprises the following steps:

[0039] S1. Preparation of SnO2 nanoparticles;

[0040] In some embodiments, the preparation method of SnO2 nanoparticles is: dissolving SnCl4·5H2O in ethylene glycol, adding anhydrous sodium carbonate solution at a certain reaction temperature, aging for a period of time, washing and drying after the reaction is completed, and calcining after grinding to obtain SnO2 nanoparticles.

[0041] In some embodiments, the molar ratio of NaCO3 to SnCl4·5H2O is 2: 1. The concentration of the anhydrous sodium carbonate solution is 0.1-0.3 mol / L.

[0042] In some embodiments, the reaction temperature is -20-100°C, which can be -20°C, -10°C, RT, 40°C, 60°C, 80°C or 100°C, or any value within the range, preferably -20 to -10°C.

[0043] The present invention adopts a coprecipitation method to prepare SnO2, and adjusts the morphology of SnO2 by controlling the reaction temperature. It is observed through SEM characterization that the SnO2 prepared at low temperature is dispersed in smaller nanoparticles. In low-temperature coprecipitation, the formation and growth of crystal nuclei are relatively slow and uniform, and it is not easy to have excessive growth or agglomeration of grains, so that catalyst particles with uniform particle size can be prepared. In addition, low temperature is also conducive to the formation of more active sites. Several SnO2 nanoparticles prepared at different temperatures are used for hydrogen detection, and it is found that the SnO2 prepared at -20°C has better hydrogen sensing performance.

[0044] The SnO2 nanoparticles prepared by the method of the present invention have a response value of 27.7 to H2 at an optimal working temperature of 200°C, and a response value of 2.63 to CO. In contrast, the SnO2 prepared by CN117554438A has a response value of 10 to CO and a response value of 8 to H2 at an optimal working temperature of 200°C, so the SnO2 nanoparticles prepared by the present invention have better sensing performance to H2.

[0045] In some embodiments, the rate of adding the anhydrous sodium carbonate solution is 1-2 mL / min. The aging time is 1-8 h. If the dropping speed is too fast, a large amount of precipitation will be precipitated and easily agglomerated, resulting in the prepared SnO2 particles being too large, affecting its sensing performance.

[0046] In some embodiments, the drying temperature is 60-100°C, and the drying time is 8-24h, wherein the drying temperature can be 60°C, 70°C or 80°C, or other values ​​within the range; the drying time can be 8h, 10h, 12h, 16h or 24h, or other values ​​within the time range.

[0047] In some embodiments, the calcination temperature is 300-500°C, and the calcination time is 3-5 hours. The calcination temperature can be 300°C, 350°C, 400°C, 450°C or 500°C, or other values ​​within the range. The calcination time can be 3 hours, 4 hours or 5 hours, or other values ​​within the range.

[0048] S2. Dissolve PdCl2 in anhydrous ethanol and disperse it by ultrasonic to obtain an ethanol solution of PdCl2.

[0049] S3. Add BCN and SnO2 nanoparticles to an ethanol solution of PdCl2, perform ultrasonic treatment (preferably for 1-4 hours), load PdCl2 and BCN onto the surface of SnO2, and after centrifugation, drying and grinding, calcine in a hydrogen atmosphere to obtain a Pd-BCN / SnO2 composite material.

[0050] The BCN (boron carbonitride) can be prepared by existing technology, for example, the preparation method is as follows: urea and boric acid are ground and then calcined. Preferably, the mass ratio of urea to boric acid is 200:1. Preferably, the calcination temperature is 600°C, the heating rate is 5°C / min, and the holding time is 4h.

[0051] The preparation method of BCN in the following example is as follows: 40 g of urea and 200 mg of boric acid are fully ground in a mortar, then placed in a covered crucible, heated to 600° C. in a muffle furnace at a heating rate of 5° C. / min, and maintained at this temperature for 4 h.

[0052] In some embodiments, the mass ratio of Pd to SnO2 is 1-3:100, preferably 2:100, and the mass ratio of BCN to SnO2 is 1-10:100, preferably 5:100.

[0053] In some embodiments, the drying temperature is 60-80°C and the drying time is 8-24h, wherein the drying temperature can be 60°C, 70°C or 80°C, or other values ​​within the range; the drying time can be 8h, 10h, 12h, 16h or 24h, or other values ​​within the time range.

[0054] In some embodiments, the calcination temperature is 100-300°C, and the calcination time is 0.5-3h. The calcination temperature can be 100°C, 150°C, 200°C, 250°C or 300°C, or other values ​​within the range; the calcination time can be 0.5h, 1h, 1.5h, 2h, 2.5h or 3h, or other values ​​within the time range.

[0055] In some specific embodiments, the gas-sensitive element of the present invention comprises an alumina ceramic tube and a gas-sensitive coating coated on the outer wall thereof, wherein the gas-sensitive coating comprises the Pd-BCN / SnO2 gas-sensitive composite material of the present invention.

[0056] In some embodiments, the gas-sensitive coating is prepared as follows:

[0057] Take an appropriate amount of Pd-BCN / SnO2 gas-sensitive material, mix it evenly with deionized water, and grind it (preferably for 20-60 minutes) to obtain a uniform paste slurry;

[0058] The paste slurry is evenly coated on the outer wall of the alumina ceramic tube so that it covers the entire ceramic tube.

[0059] In some specific embodiments, the hydrogen sensor of the present invention comprises a bakelite base, a Ni-Cr alloy heating wire, a stainless steel mesh cover and the gas sensing element. The structure thereof can be referred to in CN117554438A. Figure 1 .

[0060] In some embodiments, the coated gas-sensitive element is assembled onto a bakelite base; a Ni-Cr alloy heating wire is passed through the interior of an alumina ceramic tube, and both ends of the heating wire are welded to the bakelite base, and then covered with a stainless steel mesh cover; the assembled sensor device is subjected to an aging treatment, preferably with an aging temperature of 200°C and an aging time of 12 hours.

[0061] The gas-sensitive composite material of the present invention belongs to an n-type semiconductor, and the working principle of the gas-sensitive element is as follows:

[0062] When n-type semiconductors are exposed to air, oxygen, due to its strong electron affinity, will be adsorbed on the surface of the material and take away electrons from the conduction band to form different forms of oxygen anions (O2 - , O - , O 2- ), the existence form of adsorbed oxygen will vary with the change of working temperature: when the working temperature is lower than 150℃, the adsorbed oxygen species is mainly O2 - When the working temperature is in the range of 150℃-300℃, O2 - The ions capture electrons to form O - ions, and when the operating temperature is higher than 300 °C, the adsorbed oxygen species are converted into O 2- This adsorption process will reduce the electron concentration on the surface of the material, forming an electron depletion layer on the surface of the material, which shows high resistance; when the n-type semiconductor comes into contact with the reducing gas H2, H2 will react with the oxygen anions on the surface of the material to produce an oxidation reaction, and the released electrons will return to the conduction band, making the width of the electron depletion layer on the surface of the material narrower and the resistance reduced. The sensitivity of the sensor is calculated by the change in resistance.

[0063] The sensitivity calculation formula of the sensor device is: S = R a / R g .

[0064] Where S is the sensitivity; R a is the resistance value of the gas sensor in the air; R g It is the resistance value of the gas sensor in the target gas.

[0065] The response time calculation formula of the sensor device is: t res =|R a -R g |×90%;

[0066] The recovery time calculation formula of the sensor device is: t rec =|R g -R a |×90%.

[0067] Among them, t res The gas sensor consists of a resistor R a Change to R g The time required for the resistance to change by 90%; t rec The gas sensor consists of a resistor R g Return to the initial resistance R a The time required for the resistance to change by 90% of the difference.

[0068] Embodiment 1:

[0069] A preparation method of a Pd / SnO2 gas sensor (without adding BCN), the specific steps are as follows:

[0070] (1) 3.506 g SnCl4·5H2O was dissolved in 30 mL ethylene glycol and stirred until completely dissolved. The mixture was reacted at a synthesis temperature of -20°C. Anhydrous sodium carbonate (100 mL with a concentration of 0.2 mol / L) was added dropwise using a peristaltic pump. The flow rate was set to 1-2 mL / min and the mixture was slowly added dropwise. After the addition was completed, the mixture was aged for 1 h. The resulting precipitate was washed alternately with deionized water and anhydrous ethanol until it was neutral, dried at 80°C for 12 h, ground, and calcined in a muffle furnace at 400°C for 4 h to obtain SnO2 solid powder.

[0071] (2) According to the mass ratio of Pd and SnO2, different masses of PdCl2 were weighed and mixed with 5 mL of anhydrous ethanol, and ultrasonicated for 10 min to accelerate the dispersion and dissolution of PdCl2. 200 mg of SnO2 was added to the PdCl2 ethanol solution and ultrasonicated for 1 h. After centrifugation, the solution was placed in an oven at 60°C for 10 h and dried. After grinding, the solution was placed in a tubular furnace and calcined at 200°C for 1 h by passing H2 to obtain Pd / SnO2 black powder, wherein the mass ratio of Pd to SnO2 was 1-3:100 (the mass percentage of Pd relative to SnO2 was 1-3%).

[0072] (3) taking an appropriate amount of Pd / SnO2 composite material and mixing it evenly with deionized water, grinding it in a mortar for a period of time to obtain a uniform paste slurry; using a brush to apply the paste on the outer wall of the alumina ceramic tube so that the sample evenly and evenly covers the entire ceramic tube;

[0073] (4) After natural drying, the four platinum wires of the ceramic tube are welded to the bakelite base in sequence;

[0074] (5) Pass the Ni-Cr alloy heating wire through the inside of the alumina ceramic tube, weld both ends of the heating wire to the bakelite base, and then cover it with a stainless steel mesh cover;

[0075] (6) The assembled sensor device is subjected to aging treatment at an aging temperature of 175°C and an aging time of 12 h.

[0076] (7) Install the sensor on the test bench, inject hydrogen into the air cavity, and collect the signal.

[0077] Figure 1 The following is the response curve of Pd / SnO2 sensors with different loading amounts to 500ppm H2 as a function of temperature. Figure 1It can be seen that as the working temperature increases, the sensor response value first increases and then decreases, presenting a "volcano-type" curve. As the Pd loading increases, the sensor response value also shows a trend of first increasing and then decreasing. Among them, the 2wt% Pd / SnO2 gas-sensitive material has good gas-sensitive performance to 500ppm H2, with the highest response value of 431.27 at 100℃. Therefore, the optimal mass ratio of Pd to SnO2 is set to 2:100.

[0078] The effect of the BCN-loaded composite material on the H2 sensing performance was further explored using the optimal Pd loading amount as a quantitative measure, as shown in Example 2.

[0079] Embodiment 2:

[0080] A method for preparing a Pd-BCN / SnO2 gas sensor, the specific steps are as follows:

[0081] (1) 3.506 g SnCl4·5H2O was dissolved in 30 mL ethylene glycol and stirred until completely dissolved. The mixture was reacted at a synthesis temperature of -20°C. Anhydrous sodium carbonate (100 mL with a concentration of 0.2 mol / L) was added dropwise using a peristaltic pump. The flow rate was set to 1-2 mL / min and the mixture was slowly added dropwise. After the addition was completed, the mixture was aged for 1 h. The resulting precipitate was washed alternately with deionized water and anhydrous ethanol until it was neutral, dried at 80°C for 12 h, ground, and calcined in a muffle furnace at 400°C for 4 h to obtain SnO2 solid powder.

[0082] (2) Weigh 6.66 mg of PdCl2 and mix it with 5 mL of anhydrous ethanol, and ultrasonicate for 10 minutes to accelerate the dispersion and dissolution of PdCl2. Add 2, 6, 10, and 20 mg of BCN respectively and ultrasonicate for 10 minutes. Finally, add 200 mg of SnO2 and ultrasonicate for 1 hour. After centrifugation, put it in an oven at 60°C to dry for 10 hours. After grinding, put it in a tube furnace, pass H2 and calcine at 200°C for 1 hour to obtain Pd-BCN / SnO2 black powder, wherein the mass ratio of Pd to SnO2 is 2:100, and the mass ratio of BCN to SnO2 is 1-10:100 (the mass percentage of BCN relative to SnO2 is 1-10%).

[0083] (3) Taking an appropriate amount of Pd-BCN / SnO2 composite material and mixing it evenly with deionized water, grinding it in a mortar for a period of time to obtain a uniform paste slurry; using a brush to apply the paste on the outer wall of the alumina ceramic tube so that the sample evenly and evenly covers the entire ceramic tube;

[0084] (4) After natural drying, the four platinum wires of the ceramic tube are welded to the bakelite base in sequence;

[0085] (5) Pass the Ni-Cr alloy heating wire through the inside of the alumina ceramic tube, weld both ends of the heating wire to the bakelite base, and then cover it with a stainless steel mesh cover;

[0086] (6) The assembled sensor device is subjected to aging treatment at an aging temperature of 175°C and an aging time of 12 h.

[0087] Figure 2 This is the XRD pattern of the Pd-BCN / SnO2 gas sensitive material prepared in Example 2.

[0088] Comparative Example 1:

[0089] The preparation method of Pd / SnO2 gas sensor (without adding BCN) is as follows:

[0090] (1) 3.506 g SnCl4·5H2O was dissolved in 30 mL ethylene glycol and stirred until completely dissolved. The mixture was reacted at a synthesis temperature of -20°C. Anhydrous sodium carbonate (100 mL with a concentration of 0.2 mol / L) was added dropwise using a peristaltic pump. The flow rate was set to 1-2 mL / min and the mixture was slowly added dropwise. After the addition was completed, the mixture was aged for 1 h. The resulting precipitate was washed alternately with deionized water and anhydrous ethanol until it was neutral, dried at 80°C for 12 h, ground, and calcined in a muffle furnace at 400°C for 4 h to obtain SnO2 solid powder.

[0091] (2) 6.66 mg of PdCl2 was weighed and mixed with 5 mL of anhydrous ethanol. The mixture was ultrasonicated for 10 min to accelerate the dispersion and dissolution of PdCl2. 200 mg of SnO2 was added to the PdCl2 ethanol solution and ultrasonicated for 1 h. After centrifugation, the mixture was placed in an oven at 60°C for 10 h. After grinding, the mixture was placed in a tubular furnace and calcined at 200°C for 1 h. Pd / SnO2 black powder was obtained, in which the mass ratio of Pd to SnO2 was 2:100.

[0092] The subsequent preparation steps are the same as steps (3) to (6) in Example 1.

[0093] The sensing performance of the sensor devices in Example 2 and Comparative Example 1 was tested, and the results are as follows:

[0094] Figure 3The response value curve of 2wt% Pd / SnO2 gas sensor with different BCN doping amounts to 500ppm H2 changes with temperature. As can be seen from the figure, as the working temperature increases, the response values ​​of all sensors first increase and then decrease, presenting a "volcano-shaped curve". Among them, the response value of 2wt% Pd / SnO2 to 500ppm H2 is 431.27 at the optimal working temperature of 100℃. After adding BCN, the response value of the sensor decreases as the working temperature decreases. This shows that the addition of BCN can reduce the working temperature of the sensor and improve the sensitivity. When the BCN loading is 5%, the response value of the gas sensor is the highest. The response value of 2wt% Pd-5wt% BCN / SnO2 to 500ppm H2 is as high as 1585.85 at the optimal working temperature of 75℃. As the BCN loading increases, the sensor working temperature gradually decreases until it reaches a stable value, and the response value first increases and then decreases. It may be that when the BCN loading is too high, it will cover the active sites, resulting in a decrease in the number of active sites, thereby reducing the sensitivity.

[0095] Figure 4 The response recovery time curves of 2wt% Pd / SnO2 and 2wt% Pd-5wt% BCN / SnO2 gas sensors to 500ppm H2 at different temperatures are shown in FIG. Figure 4 (a) is the response recovery time curve of 2wt% Pd / SnO2 to 500ppm H2 at different temperatures. Figure 4 (b) is the response recovery time curve of 2wt% Pd-5wt% BCN / SnO2 to 500ppm H2 at different temperatures. As can be seen from the figure, as the temperature increases, the response / recovery time of the sensor gradually shortens. After adding BCN, the response / recovery time of the sensor at low temperature is even shorter.

[0096] Figure 5 The response / recovery time curves of 2wt% Pd / SnO2 and 2wt% Pd-5wt% BCN / SnO2 sensors at 75°C and 100°C. Figure 5 (a) is the response / recovery curve of 2wt% Pd / SnO2 sensor at 75℃. Figure 5 (b) is the response / recovery curve of 2wt%Pd-5wt%BCN / SnO2 sensor at 75℃. Figure 5 (c) is the response recovery curve of 2wt% Pd / SnO2 sensor at 100℃. As can be seen from the figure, the response / recovery time of 2wt% Pd / SnO2 is faster at the optimal working temperature of 100℃, but the response time (t res =158s) is much longer than the response time (t rec=49s), indicating that 2wt% Pd-5wt% BCN / SnO2 has a faster response speed at low temperatures.

[0097] Figure 6 The energy band diagram of the 2wt% Pd-5wt% BCN / SnO2 gas-sensitive material in Example 2 and the 2wt% Pd / SnO2 gas-sensitive material in Comparative Example 1. As can be seen from the figure, the band gap width (2.56eV) of the 2wt% Pd-5wt% BCN / SnO2 gas-sensitive material is smaller than the band gap width (3.27eV) of the 2wt% Pd / SnO2 gas-sensitive material, indicating that the addition of BCN increases the carrier concentration of the 2wt% Pd-5wt% BCN / SnO2 gas-sensitive material, causing electrons to be more easily excited and transitioned, and the activation energy of the chemical reaction is reduced. Therefore, the 2wt% Pd-5wt% BCN / SnO2 gas-sensitive material has better sensing performance at lower temperatures.

[0098] In order to illustrate the selectivity of 2wt% Pd-5wt% BCN / SnO2 gas-sensitive material, the sensor device assembled therein detects different gases under the same conditions. Figure 7 This is a comparison chart of the response values ​​of 2wt% Pd-5wt% BCN / SnO2 sensor to 500ppm different gases at an operating temperature of 75℃ and a relative humidity of 50±5%. As can be seen from the figure, the 2wt% Pd-5wt% BCN / SnO2 gas-sensitive material has a higher response value (S=1585.85) only to H2. Under the same conditions, the response values ​​to other gases are lower, indicating that the gas-sensitive material has a strong anti-interference ability and good selectivity to H2.

[0099] Figure 8 The response recovery curve of 2wt%Pd-5wt%BCN / SnO2 sensor to different concentrations of H2 at 75℃ and relative humidity of 50±5%. As can be seen from the figure, as the H2 concentration decreases, the response value of 2wt%Pd-5wt%BCN / SnO2 sensor also decreases. When the H2 concentration is 1ppm, the response value (S=1.57) can still be detected, indicating that 2wt%Pd-5wt%BCN / SnO2 gas-sensitive material can detect H2 in a wide concentration range.

[0100] Fig. 9 This is the repeatability curve of the 2wt% Pd-5wt% BCN / SnO2 sensor to 500ppm H2 at 75℃ and relative humidity 50±5%. As can be seen from the figure, after 10 consecutive rounds of response / recovery tests on the 2wt% Pd-5wt% BCN / SnO2 sensor, the response value fluctuation range is ≤5%, indicating that the sensor has good reusability at 75℃.

[0101] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Therefore, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing a Pd-BCN / SnO2 gas-sensitive composite material, characterized in that: The steps include: BCN and SnO2 nanoparticles are added to an ethanol solution of PdCl2, and ultrasonic treatment is performed to load PdCl2 and BCN onto the surface of SnO2, and then calcined in a hydrogen atmosphere to obtain the Pd-BCN / SnO2 gas-sensitive composite material; In the Pd-BCN / SnO2 gas-sensitive composite material, the mass ratio of Pd to SnO2 is 1-3:100, and the mass ratio of BCN to SnO2 is 1-10:

100.

2. The preparation method according to claim 1, characterized in that: The preparation method of the SnO2 nanoparticles is as follows: an anhydrous sodium carbonate solution is added dropwise to an ethylene glycol solution of SnCl4·5H2O to react, and the SnO2 nanoparticles are obtained by calcining.

3. The preparation method according to claim 2, characterized in that: The reaction temperature is -20 to 100°C.

4. The preparation method according to claim 2, characterized in that: The calcination temperature for obtaining SnO2 nanoparticles is 300-500°C.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The mass ratio of Pd to SnO2 is 2:100, and the mass ratio of BCN to SnO2 is 5:

100.

6. The preparation method according to any one of claims 1 to 4, characterized in that: The calcination temperature of the Pd-BCN / SnO2 gas-sensitive composite material obtained by calcination is 100-300°C.

7. A Pd-BCN / SnO2 gas-sensitive composite material, characterized in that: The method is prepared by any one of claims 1 to 6.

8. A gas sensor, characterized in that: The invention comprises an alumina ceramic tube and a gas-sensitive coating coated on the outer wall thereof, wherein the gas-sensitive coating comprises the Pd-BCN / SnO2 gas-sensitive composite material as claimed in claim 7.

9. A hydrogen sensor, characterized in that: It comprises the gas sensor according to claim 8.

10. Use of the Pd-BCN / SnO2 gas-sensitive composite material according to claim 7, or the gas-sensitive element according to claim 8, or the hydrogen sensor according to claim 9 in low-temperature H2 sensing, wherein the operating temperature is less than 120°C.

Citation Information

Patent Citations

  • Pd / SnO2 / g-C3N4 nano gas-sensitive composite material, preparation method thereof and application of Pd / SnO2 / g-C3N4 nano gas-sensitive composite material in CO sensing

    CN117554438A

  • Pd-coated Pt / In2O3 nano material and hydrogen sensor

    CN117929487A